2017
DOI: 10.1002/ejsp.2301
|View full text |Cite
|
Sign up to set email alerts
|

It is written all over your face: Socially rejected people display microexpressions that are detectable after training in the Micro Expression Training Tool (METT)

Abstract: Social rejection is a powerful negative emotional experience, yet rejected people often appear stoic and unmoved. That is, their macroexpressions of emotion are not accurate reflections of their emotional states. Yet, there is reason to believe that rejected people exhibit involuntary microexpressions of negative emotion. We contrasted people's macroexpressions of emotion with their microexpressions subsequent to an acceptance or rejection experience. Observers coded microexpressions after being trained with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…Overall, the large majority of the children in the current study reacted with facial expressions of negative emotions. This observation is in line with an earlier study on social exclusion and facial expression [ 67 ] and with results from Williams [ 4 ] and Hartgerink et al [ 5 ], who noted that the Cyberball paradigm has pervasive negative effects on participants. Further, the authors observed that effects of Cyberball are relatively robust against moderation by personal or situational factors.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the large majority of the children in the current study reacted with facial expressions of negative emotions. This observation is in line with an earlier study on social exclusion and facial expression [ 67 ] and with results from Williams [ 4 ] and Hartgerink et al [ 5 ], who noted that the Cyberball paradigm has pervasive negative effects on participants. Further, the authors observed that effects of Cyberball are relatively robust against moderation by personal or situational factors.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that both the arousing value and the subjective significance of emotional stimuli may be processed without conscious acknowledgement of noticing the stimuli may be incorporated into therapeutic work. It is already a well-known fact that implicit factors such as micro-expressions can influence our mood and, as a consequence, mental stability (McDonald et al, 2018 ; Svetieva & Frank, 2016 ); therefore, it is possible that more factors other than the pleasant or unpleasant value of such implicit stimuli should be taken into account when analyzing its influence. The exploration of influence of four separate emotional factors on decision making, with clear results regarding the decisions themselves, also contributes to the field of research in subliminal affective priming paradigm, as most of the studies do not explore the factors of origin and subjective significance (Nava & Turati, 2020 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, we cannot assess the impact of the ERT on recognition rates; this also prohibits us from analysing the relationship between ERT and lie-types (e.g., how SETT scores correlate with emotional lie detection as in Warren et al, 2009). Nonetheless, our protocols mirror the standards in the field (e.g., Jordan et al, 2019; Warren et al, 2009), employing tools which produce reliable effects (e.g., Hurley, 2012; Matsumoto & Hwang, 2011; McDonald et al, 2018). Second, the videos were not coded for emotional cues, nor did we question decoders whether they had relied on such information given that self-reports rarely provide accurate insights into judgement processes.…”
Section: Studymentioning
confidence: 99%